Hyperbaric Oxygen Therapy Promotes Hearing Gain with Increases in Serum IGF-1 and HSP70 in Patients with Idiopathic Sudden Sensorineural Hearing Loss. (25th October 2022) - Zhang, Yi; Jia, Xingyuan; Liu, Xuehua; Zhao, Lin; Zhou, Yan; Liang, Fang; Gao, Yu; Yang, Jing
Abstract : Objective . Hyperbaric oxygen therapy (HBOT) has been recommended for the initial and salvage treatment of patients with idiopathic sudden sensorineural hearing loss (ISSHL), but its underlying mechanisms remain unclear. In this study, we investigated whether HBOT alters serum levels of insulin-like growth factor 1 (IGF-1) and heat shock protein 70 (HSP70) in patients with ISSHL. Then, we identified the relationship between hearing recovery and changes in serum IGF-1 and HSP70 levels. Methods . Moderately severe to profound unilateral ISSHL patients ( n  = 70) and healthy control participants ( n  = 30) were enrolled. The ISSHL patients were randomly assigned to receive medical therapy alone (MT group, n  = 35) or both HBOT and medical therapy (HBOT + MT group, n  = 35). Audiometric testing was performed before and after treatment. Serum IGF-1 and HSP70 levels were assessed by ELISA in ISSHL patients pre-and posttreatment and healthy controls. Results . Before treatment, compared with the healthy controls, serum IGF-1 and HSP70 were lower in ISSHL patients. After treatment, serum IGF-1 and HSP70 increased in both the HBOT + MT and MT groups, although they were significantly higher in the HBOT + MT group (p < 0.01 ). In the HBOT + MT group, these increases were associated with hearing gains. In addition, IGF-1 was strongly associated with HSP70 ( r  = 0.621, p = 0.001 ). No such association was found in the MT group (p = 0.757 ). Conclusion . Administering HBOT in addition to medical therapy can improve the hearing of patients with moderately severe to profound unilateral ISSHL. The improvement is related to the upregulation of IGF-1 and HSP70.